Dealing with project characteristics through concurrent product development by Malaysian car producer - Boejang, Hambali; Arep @ Ariff, Hambali; Hassan, Muhammad Zahir; Esa, Saharudin (World Academy of Research in Science and Engineering, 2019)
This research work explores and identifies the new product development (NPD) project complexity and its sources of a small-sized (low volume) car manufacturer in Malaysia. It explains the approach used by this producer to overcome the project characteristics as well. In order to understand the research topic, related literatures were reviewed and information was gathered to develop questionnaire. Later, the questionnaire was pre-tested prior to the interview sessions with relevant respondents from various functions. The feedback was used to identify and specify the source of project complexity, the types of product development projects, and the approaches adopted by the producers to vanquish project complexity. The results show that the producer defines the type of development projects and the level of project complexity according to the change contents of the vehicle and the powertrain. The car producer mitigates and eliminates project complexity and uncertainty through the adoption of concurrent engineering practices, robust planning, and co-development. However, the product radical innovation is not the factor that really affects the project complexity in the new product development effort for this Malaysian small-sized car producer.